(untitled) (Journal of Management and Social Sciences, 2024)
Osun State has been one of the beneficiaries of Nigeria’s Conditional Cash Transfer Programme (CCTP) since its inception in 2016. This study provides a comparative analysis of the poverty status of beneficiaries before and after the implementation of the CCTP in Osun State. The study adopts a descriptive research design. A multi-stage sampling process was employed to select participants from the programme. The population of the study consists of CCTP beneficiaries across the three senatorial districts of Osun State, with a sample size of 360 beneficiaries selected using a stratified sampling technique. Questionnaires were used for data collection. The collected data was analysed using descriptive and inferential statistical tools. The findings of the study reveal that beneficiaries of conditional cash transfers were poor before the implementation of the programme. The study also reveals that the poverty level of the beneficiaries reduced after programme implementation. The study, in essence, shows that there is a significant difference in the poverty status of beneficiaries before and after the implementation of the CCTP in Osun State. The study, therefore, concludes that the Nigerian government should intensify its effort to extend the CCTP to the nooks and crannies of the country so that many poor Nigerians can benefit from the programme.